Perlindungan Hukum Terhadap Anak Korban Tindakan Pemaksaan Persetubuhan yang dilakukan oleh Anak (Studi Kasus : Putusan Nomor 13/Pid.Sus-Anak/ 2019/ PN.Srg) - Andre Gunawan; Ridwan Ridwan (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2021)
Losses caused by acts of sexual intercourse, of course, affect the psychological and psychological aspects of children who are victims of sexual intercourse, legal protection is the main thing for children to receive legal assistance such as compensation and restitution and medical assistance that has been regulated in laws and regulations, judges in deciding cases of course must look at the sources of law in force today, the opinions of experts and jurisprudence, so that what the victim needs can be fulfilled. Based on this background, the problems studied in this study are legal protection for children who are victims of forced sexual intercourse by children (case study: Decision Number 13/pid.sus-anak/ 2019/pn.srg) and the legal protection provided. by law enforcement or related institutions in this case the Witness and Victim Protection Agency to victims of forced intercourse. the results of interviews in the field, indeed the victims did not apply for restitution. According to the public prosecutor's opinion, restitution was not requested in the Aries case, so it was not included in the charge which was later not included in the judge's decision. The consideration of the public prosecutor not to include a claim related to compensation is that the victim did not ask for compensation and already considered what happened as fate. The research used is a qualitative normative juridical research. This research is descriptive analysis. data source is secondary data then analyzed qualitatively. This research is descriptive analysis. The results of the research show that Decision Number 13/Pid.Sus/2019/PN.Srg has not provided legal protection for victims of forced intercourse. This can be seen in the absence of restitution or compensation for victims in the decision. The judge's decision is more oriented towards punishment for the perpetrators, but has not considered the restoration of the rights of the victims. Even though the regulation of victim protection already exists, in law enforcement this case still uses the paradigm of punishment for the perpetrator without the fulfillment of the victim. Legal protection for children who are victims of forced intercourse is necessary because the state has guaranteed protection for its citizens and laws and regulations have regulated legal protection for every community who is in conflict with the law. for the sake of creating justice and welfare for the community, law enforcement officers in this case the panel of judges in deciding cases should pay attention to the applicable laws and regulations, so that in deciding cases in court the creation of a just law, legal protection can be realized if law enforcement can be applied by law enforcers. law.